2015
DOI: 10.1002/nau.22740
|View full text |Cite
|
Sign up to set email alerts
|

Two‐years results of native tissue versus vaginal mesh repair in the treatment of anterior prolapse according to different success criteria: A randomized controlled trial

Abstract: Transvaginal synthetic mesh repair for advanced anterior vaginal prolapse provided higher anatomical success and satisfaction rates compared with traditional colporraphy. Both procedures equally improved quality of life. Neurourol. Urodynam. 35:509-514, 2016. © 2015 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 30 publications
2
24
0
Order By: Relevance
“…It was found that 7.7% (72/933) of women who underwent a mesh repair also had surgery for mesh exposure. This evidence is further supported by recent studies [26, 27]. …”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…It was found that 7.7% (72/933) of women who underwent a mesh repair also had surgery for mesh exposure. This evidence is further supported by recent studies [26, 27]. …”
Section: Resultssupporting
confidence: 89%
“…At 3 years follow-up, the objective anatomic cure rate was 91.4% for the mesh group and 41.2% for the colporrhaphy group. A more recent randomized study also showed a significant difference of efficacy between the trocar-guided Nazca TC ® kit and anterior colporrhaphy groups [27]. The trial reported on 86 patients with an anterior compartment prolapse stage 2 or more, according to the POP-Q system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixty-eight randomised trials, reporting data from 10,499 participants, met the inclusion criteria (Table 1) [5, 1088]. Additionally, 12 randomised trials published long-term follow-up data [5, 22, 29, 39, 40, 64, 71, 72, 79, 81, 86, 87]
Fig. 1Study search and inclusion
…”
Section: Resultsmentioning
confidence: 99%
“…While the use of a transvaginal mesh has been shown to be both subjectively and objectively more effective than anterior colporrhaphy [ 4 ], many complications related both to the mesh and to the transobturator approach have been described [ 1 , 7 , 8 ]. The transobturator procedure involves inserting two needles in both obturator areas without visual control.…”
Section: Introductionmentioning
confidence: 99%